CONDIÇÕES SOCIAIS PARA A ATRATIVIDADE, O ACESSO E A PERMANÊNCIA NAS LICENCIATURAS DA UEPG - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This dissertation’s main theme is teacher’s valorization policies, which involve primarily teachers training, work conditions, career and remuneration. Along the text, we seek to unveil the hidden specificities in the initial teachers training process. Therefore, we aim to answer the following question: which are the social conditioners for the teacher’s career choice, in view of the access and permanence in the graduations within teacher preparation program at the State University of Ponta Grossa (UEPG)? On that account, we objectively analyze the main determinants that guide the students to choose the teaching career and their influences in the access and permanence conditions in these graduations. In the path to reach our aim, we look for the Marxist methodologic theory, the dialectical and historical materialism. To collect data, we applied a 67 objective questions questionnaire to the students of the senior year (4th) of 2017 in the following courses: Visual Arts, Biological Sciences, Physical Education, Physics, Geography, History, English Language and its Literature, Mathematics, Music, Pedagogy and Chemistry. In the questionnaire the socio-economical, institutional, familiar and personal aspects were taken into account. In 2018, semi-structured interviews were held within six university egresses from the same courses the questionnaire was applied, aiming to depth some aspects of this collecting tool. According to the data, most of the students are working people, from the public system of elementary education and high school, with family income until three Brazilian minimum wage, have had thoughts of giving up their graduation and felt/feel the need of student assistance, mostly related to transport and feeding. Thus, considering that the work precarious organization in the capitalist society in its turn creates the precariousness in the workers training/preparing programs. Hence, we understand that the teacher career choice and the graduation access are conditioned mostly by the need to work. The permanence is only possible due to the conciliation of work and graduation. That being the case working is the element for both allowing the student to stay in their course and disqualify its development, as well as the reason for them to leave. Therefore, working, studying and becoming a teacher is a resignation and resistant act towards the capital. Resistant because being a working person within unwealthy socio-economical conditions as well as a student goes against the perspective that working people should only work to reproduce the workforce. With this research, we pretend to contribute within the political emancipation through the knowledge of the reality that follows the initial teacher preparation program at UEPG, as so we can change this reality with policies that meet the demands here presented. Yet, not having out of sight that only by human emancipation we truly can free ourselves from the barriers imposed by the capital in all the different aspects of life.
Keywords: Política educacional; Valorização docente; Atratividade para a carreira docente; Acesso e permanência nas licenciaturas da UEPG; Educational policies; Teachers valorization; Teaching career atractiveness; Access and permanece graduation within teacher preparing program; CNPQ::CIENCIAS HUMANAS::EDUCACAO